Functional MRI–Guided Motor Cortex and Deep Brain Stimulation for Intractable Facial Pain: A Novel, Personalized Approach in 1 Patient. Issue 1 (17th January 2023) - Saway, Brian Fabian; Webb, Timothy; Weber, Aimee; Triano, Matthew; Barley, Jessica; Spampinato, Maria; Rowland, Nathan
Abstract : BACKGROUND: Facial neuropathic pain syndromes such as trigeminal neuralgia are debilitating disorders commonly managed by medications, vascular decompression, and/or ablative procedures. In trigeminal neuralgia cases unresponsive to these interventions, trigeminal deafferentation pain syndrome (TDPS) can emerge and remain refractory to any further attempts at these conventional therapies. Deep brain stimulation (DBS) and motor cortex stimulation are 2 neuromodulatory treatments that have demonstrated efficacy in small case series of TDPS yet remain largely underutilized. In addition, functional MRI (fMRI) is a tool that can help localize central processing of evoked stimuli such as mechanically triggered facial pain. In this study, we present a case report and operative technique in a patient with TDPS who underwent fMRI to guide the operative management and placement of dual targets in the sensory thalamus and motor cortex. OBJECTIVE: To evaluate the safety, efficacy, and outcome of a novel surgical approach for TDPS in a single patient. METHODS: The fMRI and operative technique of unilateral DBS targeting the ventroposteromedial nucleus of the thalamus and facial motor cortex stimulator placement through a single burr hole is illustrated as well as the patient's clinical outcome. RESULTS: In less than 1 year, the patient had near complete resolution of his facial pain with no postoperative complications. CONCLUSION: We present the first published case of successful treatment of TDPS using simultaneous DBS of the ventroposteromedial and motor cortex stimulation. fMRI can be used as an effective imaging modality to guide neuromodulation in this complex disorder.